Chile's Monitoring and Evaluation System, 1994-2010 - Dussauge Laguna, Mauricio I. (World Bank, Washington, DC, 2012)
The Chilean Management Control and Evaluation System (Sistema de Evaluacion y Control de Gestion) is internationally regarded as a successful example of how to put into place a monitoring and evaluation (M&E) system. Chilean M&E tools are the product of both cross-national lesson-drawing, and national policy learning experiences. The main M&E tools are centrally coordinated by the Ministry of Finance's Budget Office (Direccion de Presupuestos, or DIPRES) and promote the use of M&E information in government decision-making processes, particularly those related to the budget. These M&E tools have been, however, subject to a number of criticisms. As a result, the experience described in this note does not necessarily offer a model that can, or should, be easily transferred to other countries with different institutional contexts. Furthermore, this note does not reflect the latest changes, nor does it try to offer guidance for the future. However, the Chilean experience summarized here, covering the period of 1994-2010, provides interesting examples and highly relevant lessons about the benefits and limitations of M&E design and implementation.